Symbiotic view of Provenance in Cyber Infrastrcuture and Information Security - et. al., Kukatlapalli Pradeep Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Access control is one of the important elements in providing confidentiality to the secured data. Access specifiers helps us understand degree of rights given to the users in utilizing data records in a right manner. Tampering the records by unauthorized parties is a high concern in secure communication. Tamper detection plays an important role in trouble shooting an issue associated with network/ host intrusion scenario. The advances in computer technology has driven the contemporary world to focus on the World Wide Web for digital data and associated information. People across the globe rely on the internet for all the data from local information to distribution of personal data through heterogeneous networks. Technology and software tools has grown so broad to an extent, where almost all of the financial transactions are taking place through online portals. On the other hand, there has been high growth in the security coercions towards user’s sensitive data. This information is however shared by the online users while performing financial transaction in e-commerce portals. In order to maintain security mechanism over the untrusted networks various authentication techniques available in this regard. All these security procedures are said to be stubborn and adequate on contextual basis, on the other hand over a period of time the intruders find out means to break into systems. Data theft and intrusion into the information systems would increase on a daily basis if defensive measures are not in place. We integrate concepts of secret sharing and data provenance to provide an indigenous solution for parameters of information security namely confidentiality, integrity and availability.